Corruption and Firm Value: Evidence from Emerging Market Economies. Issue 4 (16th March 2021) - Thakur, Bhanu Pratap Singh; Kannadhasan, M; Charan, Parikshit; Gupta, C. P.
ABSTRACT: We examine the effect of corruption on firm value using a comprehensive panel data set of 4236 firms with 38, 763 firm-year observations from 16 emerging market economies during 2002–2015. By using fixed-effects panel data regression models, we find a significant negative relationship between firm value and corruption. The results are also robust to subsample analyses and to the alternate measure of firm value and corruption. Overall, our study provides evidence that corruption in emerging market economies has a negative impact on firm value. Furthermore, our study contributes to the existing literature on the drivers of firm value.